REGULAMENTAÇÃO DA INDÚSTRIA DO PETRÓLEO: ESTUDO DE CASO SOBRE A CRIAÇÃO DA RESOLUÇÃO CONAMA 293 UM MODELO A SER ADOTADO - Molle Junior, Luiz (2004)
This study (Oil industry regulation: case study on the CONAMA Resolution 293 elaboration process a model to be adopted)) shows, based on analysis of the elaboration process of a specific regulation to potentially impacting economic activity petroleum exploration and production (E&P) that regulations made through the direct involvement of all interested parties trend to be more adequate than others made by only one of then, isolated. The author considers particularly the elaboration of a milestone regulation for the Brazilian oil industry, since petroleum is being the main source of energy to the country and worldwide during the last century, according to International Energy Agency (IEA) statistics, and also for the next 20 years (IEA, 2003). In this context, considering the strategic position of the product and the impact of costs to the Brazilian energy matrix, as well as the environmental impact of the use of oil, the author shows and evaluates the elaboration process of a specific regulation for oil spill emergency plan to the E&P activity. The author sows the evolution on the use of the petroleum by the humankind especially during the last century world trends on such use, statistics and environmental impacts caused by oil spill and, mainly in the last decades, movements on the direction of a sustainable development by society that, one hand needs development and on the other hand, cannot avoid adequate regulation in order to assure this development is based on environmentally safe procedures. Finally, the author shows and analyses the elaboration process of the CONAMA (National Council of Environment) Resolution 293 which establishes criteria for oil spill emergency plans for certain installations as a standard process to be adopted on the elaboration of regulations, especially those with wide range of social and economic interests, in order to integrate social, environmental and economic point of view. Concludes based on analysis of the elaboration process of the regulation and a comparison between the final document (CONAMA Resolution 293) and documents used during the process that intensive interaction of interested parties is the best way to obtain such regulatory standards instead of those made by only one or another, isolated.